Occurrence of virulent multidrug-resistant Enterococcus faecalis and Enterococcus faecium in the pigs, farmers and farm environments in Malaysia - Tan, S.C.; Chong, C.W.; Teh, Cindy Shuan Ju; Ooi, P.T.; Thong, Kwai Lin (PeerJ, 2018)
Background Enterococcus faecalis and Enterococcus faecium are ubiquitous opportunistic pathogens found in the guts of humans and farmed animals. This study aimed to determine the occurrence, antimicrobial resistance, virulence, biofilm-forming ability and genotypes of E. faecalis and E. faecium from swine farms. Correlations between the genotypes, virulotypes, antibiotic resistance, and the environmental factors such as locality of farms and farm hygiene practice were explored.